2023
DOI: 10.1080/21645515.2023.2168936
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ willingness to pay for their children’s COVID-19 vaccine in Taiwan, China: A cross-sectional study

Abstract: Most COVID-19 studies aim to assess factors influencing willingness to pay for vaccines between the public and medical staff. However, few studies focus on parents’ willingness to pay for their children’s COVID-19 vaccine. The current study aimed to assess parents’ willingness to pay for their children’s vaccination against COVID-19 and its influencing factors. This population-based cross-sectional study used a self-administered questionnaire. The inclusion criterion was parents with at least one child younger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The increase in parental willingness could be attained through different aspects, such as using Zoom-focused education and minimizing the pay for the vaccine. 49 An introduction of ZOOM sessions and empowerment of parents to ask their concerns related to vaccines to HCPs during these sessions reported 65% improved vaccination compliance in Hong Kong preschoolers. 50 Clear and appropriate communication with caregivers and parents related to the benefits of vaccination and awareness related to safety precautions help improve the rate of vaccination among children.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in parental willingness could be attained through different aspects, such as using Zoom-focused education and minimizing the pay for the vaccine. 49 An introduction of ZOOM sessions and empowerment of parents to ask their concerns related to vaccines to HCPs during these sessions reported 65% improved vaccination compliance in Hong Kong preschoolers. 50 Clear and appropriate communication with caregivers and parents related to the benefits of vaccination and awareness related to safety precautions help improve the rate of vaccination among children.…”
Section: Discussionmentioning
confidence: 99%
“…The contradiction may be explained by vaccination promotion efforts. When the majority of people considered the price to be too high when the expected Chinese vaccine price was about 1,000 RMB in August 2020 [ 48 ], numerous strategies were adopted in China to facilitate vaccine uptake [ 49 ], some of which may have had a positive impact on WTP, such as health communication campaigns [ 50 ]. In September 2020, the Chinese public already favored a vaccine price of 600 RMB [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Li et al argued that highly educated individuals are usually capable of making the right vaccination decisions and, thus, less educated individuals are more hesitant about vaccines, but both scholars agreed that knowledge is an important factor influencing vaccine hesitancy, and Li also found that vaccine hesitation was influenced by age, with older individuals being more hesitant about vaccines [18]. Reiter et al found that individuals with lower socioeconomic status or no health insurance were more likely to be vaccine-hesitant [48] and that aggressive vaccine payment policies may promote COVID-19 vaccination [49]. Low income is a barrier to vaccination, but it has also been shown that households with higher income levels are more able to cope with the adverse effects of disease and, thus, have higher levels of vaccine hesitancy [50].…”
Section: Vaccine Hesitancymentioning
confidence: 99%